A comparative study of a quasi 3D woven composite with UD and 2D woven laminates. (December 2020) - Zhou, Wu; Wente, Tony; Liu, Dahsin; Mao, Xinyu; Zeng, Danielle; Torab, Homa; Dahl, Jeff; Xiao, Xinran
Highlights: The Q3D achieved the same in-plane tensile property as the UD composite. The Q3D significantly improved the resistance to interlaminar crack growth. The energy absorption capability of the Q3D composite was 5–7% higher. Under lateral impact, the Q3D displayed a different damage pattern. Abstract: To develop a composite with high in-plane properties and sufficient delamination resistance, a quasi-three-dimensional (Q3D) woven composite has been designed. In Q3D, some yarns in each layer are woven into those in the adjacent layers and form a 3D interlocking network. This study examines the performance of a carbon fiber/SC-15 epoxy triaxial Q3D [(0°/60°/−60°)4 ] composite. For comparison, a [0°/60°/− 60°]4 composite laminate with unidirectional (UD) plies and a [0°/60°/−60° ]4 laminate with two-dimensional woven (2DW) layers were fabricated using the same carbon fiber and epoxy system. The in-plane tensile, interlaminar fracture, and low-velocity impact tests were performed for all three types of composites. The results show that the Q3D composite has the in-plane tensile modulus and strength comparable to that of UD and 2DW composites, but offers a higher resistance to interlaminar crack propagation and impact damage. This work provides insights into the influences of fiber structures on composite properties and performances.